Cytochrome P450 1A2 co-determines neuroleptic load and may diminish tardive dyskinesia by increased inducibility. (April 2015) - Ivanova, Svetlana A.; Toshchakova, Valentina A.; Filipenko, Maxim L.; Fedorenko, Olga Yu; Boyarko, Evgenia G.; Boiko, Anastasia S.; Semke, Arkadiy V.; Bokhan, Nikolay A.; Aftanas, Lyubomir I.; Loonen, Anton J.M.
Abstract: Objectives. The aim of this study was to investigate a possible association between tardive dyskinesia (TD) and CYP1A2 (*1F, -163C>А, rs762551) polymorphism in Russian psychiatric inpatients. Methods. TD was assessed cross-sectionally using the Abnormal Involuntary Movement Scale (AIMS). Orofacial and limb-truncal dyskinesia were assessed with AIMS 1–4 and 5–7, respectively. Standard protocols were applied for genotyping. Analysis of covariance (ANCOVA) was used to compare the mean AIMS scores for each of the genotypic classes. Results. A total of 319 Caucasian patients from West Siberia with schizophrenia and 117 healthy volunteers were investigated. No significant differences between the patients and the controls in genotype frequencies were found. Analysis of covariance (ANCOVA) with age, sex, duration of disease, chlorpromazine equivalent (CPZEQ) incorporated as covariates showed that limb-truncal, but not orofacial TD, is associated with CYP1A2 (−163C>, rs762551) polymorphism ( F = 3.27, P = 0.039). Patients with the C/C genotype had a higher mean AIMS 5–7 score than those with the A/C or the A/A genotype. Conclusions. Our results support the hypothesis that not only with clozapine, but also with other classical and atypical antipsychotics, smoking may decrease plasma levels; this is most extensively expressed in carriers of the CYP1A2*1F (-163C> A) polymorphism.